Kajian Kurikulum Fiqih Pada Madrasah Aliyah Di Kabupaten Sambas Kalimantan Barat Pada Masyarakat Perbatasan - Aslan, Aslan (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2018)
The curriculum is a journey of people from day to day to achieve a desired goal. Likewise the case with existing curricula at home carried out by parents, school curricula carried out by teachers and community curricula carried out by the community through community institutions. The curriculum in jurisprudence is closely related to human life, both in the procedures of worship, community and social phenomena that occur in the current era of information or in the age of the 21st century. Therefore, the social symptoms experienced by traditional society towards modern society , especially in the Border Sambas community where various problems occur in the community with various kinds of schools, so that as a teacher, they must be observant in teaching students about this fiqh problem. Because, if the fiqh teacher is not professional in accordance with his field of fiqh science, it is like one drop of poison inserted in glass water resulting in the death of more than one person